Collect Once - Use Many Times: The Research Potential of Low Back Pain Patients' Municipal Electronic Healthcare Records - Toftdahl, Anne Katrine Skjølstrup; Pape-Haugaard, Louise Bilenberg; Palsson, Thorvaldur Skuli; Villumsen, Morten (Building Continents of Knowledge in Oceans of Data: the Future of Co-Created EHealth, 2018)
Collect Once - Use Many Times can possibly increase the research potential of clinical data from electronic healthcare records (EHR). The objective of this study was to achieve an increased understanding of the research potential of low back pain patients' municipal EHR by assessing the data quality. This explanatory sequentially mixed-methods case study consists of descriptive- and content analysis. The descriptive analysis was based on data extracted from the municipal EHR. The indicators chosen were pain and physical function. Included subjects were low back pain patients in the Northern Denmark. For the content analysis, clinical notes from the municipal EHR was used. The descriptive analysis (n=172) showed that the outcome measure for pain was documented in 50% of the municipal EHR and the outcome measure for physical function was documented in 48% of the municipal EHR. The content analysis (n=5) revealed imprecise, inconsistent, and nonsystematic use of outcome measures. In conclusion, the poor data quality observed is a potential barrier for introducing the Collect Once - Use Many Times paradigm, which is a prerequisite for reusing clinical data for quality assessment and research purposes.